Pseudo-Participation in Sustainable Development Programs: A Critical Reflection on Indonesian Local Cases - Sulistyowati, Fadjarini; Dibyorini, MC. Candra Rusmala; Tyas, B. Hari Saptaning; Puspitasari, Condrodewi (UIN Sunan Kalijaga, Yogyakarta, Indonesia, 2023)
It is expected that the central government promotes sustainable development goals (SDGs) to enhance social participation and inclusivity in creating sustainable livelihoods at the village level. Although the Indonesian government has implemented policies to increase stakeholder awareness, there are still restrictions on inclusive participation, limiting the democratic process. This paper aims to analyse the promotion of SDGs in Terong Dlingo Village, Bantul Regency, Indonesia, focusing on regulatory aspects and social participation. The research adopts a case study approach using qualitative methods, including observations and in-depth interviews with local practitioners. The findings reveal that the SDGs village program is largely influenced by a top-down approach, despite efforts made by individuals, families, neighbourhoods, and other elements through surveys conducted on SDGs villages. In response, the researchers suggest that greater efforts are needed to effectively socialise and supervise the program to raise awareness among the local population regarding the benefits of SDGs village programs. It is recommended that an effective socialisation and communication strategy be implemented to encourage continuous local participation in this program.